Pesantren-Based Transformational Leadership in the Development of International Madrasah Innovation - Humaisi, M. Syafiq; Thoyib, Muhammad; M. Nurdin; Ryan Rahmawati; Ngoh, Badru (IAIN Ponorogo, 2024)
This study describes how transformational leadership is the key to success in leading madrasah towards realizing competitive madrasah in the future, supported by high innovation and quality. This research was a case study with a qualitative approach. This research focused on pesantren-based transformational leadership in developing international madrasah innovation at MA Nurul Jadid Probolinggo. The research result shows that 1) the leadership idealism of the madrasah head is able to increase the commitment of madrasah stakeholders, realizing the integration of the international-national curriculums digital-based infrastructure; 2) the inspirational motivation of the madrasah head is able to provide encouragement to subordinates and to hone the potential of teachers, students, and education staff through innovative training so that they are able to achieve various awards; 3) the intellectual leadership stimulus in the form of madrasah head’s role as an agent of social change and problem-solving leader; 4) the Individual awareness of madrasah leadership in madrasah development is reflected in the ability of madrasah head to meet human resource needs according to global competency demands.